E0402 The expression and relation of the vitamin D3 up-regulated protein 1 in peripheral blood mononuclear cells from patients with coronary artery disease. (17th November 2010) - Xing, Shui; Zhen, Wu
Abstract : Aims: Vitamin D3 up-regulated protein 1(VDUP1) is a stress-response gene and participates in oxidative stress, inflammation, apoptosis, proliferation, glucose homeostasis and lipid metabolism. All of these biological effects play important roles in atherosclerosis. Hence, we made an attempt to study the gene expression of VDUP1 using PBMCs from patients with coronary artery disease (CAD). Methods: The total RNA of PBMCs were acquired from 20 normal persons without history of cardiovascular disease and 72 patients with CAD. The CAD group was divided into 6 subgroups judged by following risk factor. The subgroup 1 was patient without hyperlipidaemia, hypertension and diabetes. The subgroup 2 was patient with hypertension only. The subgroup 3 was patient with hyperlipidaemia only. The subgroup 4 was patient with diabetes only. The subgroup 5 was patient with hyperlipidaemia plus hypertension. The subgroup 6 was patient with diabetes plus hypertension. The expression of mRNA level were identified by Real-time RT-PCR. Results: The ratios of VDUP1/β-Actin of two groups were skewed distribution. In CAD group, the maximum was 630.346, the minimum was 1.000, the median was 5.205. In control group, the maximum was 837.532, the minimum was 2.395, the median was 80.449. By logarithmic transformation, the results indicated the expression of VDUP1 in PBMCs from patients with CAD were markedly down-regulated than that from control group (p<0.05). The expression of VDUP1 in PBMCs from patients with single risk factor were down-regulated than that from patients with multiple risk factors in CAD group (P2 =0.044, P4 =0.033). Conclusion: These findings shed new light onto the mechanisms of CAD, demonstrate that the expression of VDUP1 in PBMCs from treated patients with CAD has a negative correlation to CAD, and sugguest that modulating the function of VDUP1 may open a new era of the therapy for CAD.